2020
DOI: 10.18632/aging.202309
|View full text |Cite
|
Sign up to set email alerts
|

Fucoxanthin attenuates LPS-induced acute lung injury via inhibition of the TLR4/MyD88 signaling axis

Abstract: Acute lung injury (ALI) is a critical clinical condition with a high mortality rate. It is believed that the inflammatory storm is a critical contributor to the occurrence of ALI. Fucoxanthin is a natural extract from marine seaweed with remarkable biological properties, including antioxidant, anti-tumor, and anti-obesity. However, the anti-inflammatory activity of Fucoxanthin has not been extensively studied. The current study aimed to elucidate the effects and the molecular mechanism of Fucoxanthin on lipopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 40 publications
2
24
0
Order By: Relevance
“…In terms of antioxidant capacity, fucoxanthin contains a unique chemical structure (Supplementary Figure S1) including a propadiene bond and 5,6-monocyclic oxides with an enhanced antioxidant capacity [37]. Published studies have shown that fucoxanthin has unique advantages in the treatment of several oxidative stress-related diseases, such as ischemic stroke, subarachnoid hemorrhage, acute lung injury, and atherosclerotic cardiovascular disease [38][39][40][41]. In addition, as an edible carotenoid, fucoxanthin has a good safety profile.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of antioxidant capacity, fucoxanthin contains a unique chemical structure (Supplementary Figure S1) including a propadiene bond and 5,6-monocyclic oxides with an enhanced antioxidant capacity [37]. Published studies have shown that fucoxanthin has unique advantages in the treatment of several oxidative stress-related diseases, such as ischemic stroke, subarachnoid hemorrhage, acute lung injury, and atherosclerotic cardiovascular disease [38][39][40][41]. In addition, as an edible carotenoid, fucoxanthin has a good safety profile.…”
Section: Introductionmentioning
confidence: 99%
“…According to these findings, this carotenoid (200 mg/kg) improved LPS-induced depressive and anxiety-like behaviors via suppression of NF-κB and its proinflammatory target genes iNOS, COX-2, IL-1β, IL-6, and TNF-α, as well as activation of AMPK [292]. In addition, FX treatment demonstrated antifibrotic actions in bleomycin-induced pulmonary fibrosis in mice [293], as well as antiasthmatic effects in an ovalbumin-induced asthma mouse model [294,295].…”
Section: In Vivo Studiesmentioning
confidence: 89%
“…Acute lung injury (ALI) is a series of clinical syndromes caused by damage to alveolar epithelial cells and capillary endothelial cells, which mainly manifest as diffuse alveolar parenchymal injury and refractory hypoxemia, while some severe cases may develop into acute respiratory distress syndrome (ARDS). [1][2][3] ALI is typically characterized by increased respiratory rate, pulmonary edema, progressive hypoxemia, and respiratory distress, and is associated with high mortality rates. 4 ALI has been reported in clinical cases with severe acute respiratory syndrome (SARS), 5 which is prevalent in 2003, and in the current global outbreak of coronavirus disease (COVID-19), 6 manifesting as diffuse alveolar damage, hyaline membrane formation, and interstitial thickening, with severe cases resulting in pulmonary fibrosis and ARDS.…”
Section: Introductionmentioning
confidence: 99%